Altered expression of microRNA‐365 is related to the occurrence and development of non‐small‐cell lung cancer by inhibiting TRIM25 expression. Issue 12 (17th May 2019) - Han, Qian; Cheng, Peng; Yang, Hongjie; Liang, Hengpo; Lin, Fengchun
Abstract: The purpose of this current study is to elucidate whether altered microRNA‐365 (miR‐365) has an association with the initiation and development of non‐small‐cell lung cancer (NSCLC) by targeting TRIM25 expression. The expression of miR‐365 and TRIM25 in NSCLC tissues, adjacent normal tissues, and NSCLC cell lines were detected. The relationship between miR‐365 expression and TRIM25 with the clinicopathological characteristics of NSCLC was analyzed. The putative binding site between miR‐365 and TRIM25 was determined by luciferase activity assay. miR‐365 inhibitors and miR‐365 mimics were transfected to human NSCLC A549 cells, and the cell viability was detected by cell counting kit‐8 assay; flow cytometry was carried out to determine cell cycle and apoptosis rate. Poorly expressed miR‐365 and overexpressed TRIM25 was found in NSCLC tissues. TRIM25 was determined as a target gene of miR‐365. The miR‐365 and TRIM25 expression were related to the clinicopathological features of NSCLC, such as pathological classification, differentiation degree, TNM stage as well as lymph node metastasis. miR‐365 suppressed the expression of TRIM25 and elevated the expression of the proapoptotic protein in NSCLC cells. Our study demonstrates that altered expression of miR‐365 has a close association with the occurrence and development of NSCLC by inhibiting TRIM25 expression.